Prevalence and risk factors of low birth weight in East Nusa Tenggara, Indonesia - Khrispina Owa; Marieta Kristina Sulastiawati Bai (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Low birth weight (LBW) is a public health problem and is one of the causes of neonatal death in Indonesia. The Indonesian Demographic Health Survey (IDHS) in 2012 showed that the neonatal mortality rate in East Nusa Tenggara was 26/1000 live births with the most common cause of death being LBW at 10/1000 live birth rates. The profile of the Ende District Health Office in 2014 showed that the neonatal mortality rate was 12/1000 live birth rates, of which 15% were caused by low birth weight. Purpose: To determine prevalence and risk factors of low birth weight in East Nusa Tenggara, IndonesiaMethod: The study was conducted in six public health centers in Ende Regency, NTT Province. The research design was a case-control with 156 respondents. In the case group the infants who birth weighing <2500 grams as many as 78 while the control group was 78 who gave birth to babies with a normal birth weight of 2500 grams and selected randomly from the birth register in 2015. Data were collected from the examination card of pregnant women, the MCH handbook, and by interviews with each respondent. Data were analyzed bivariate (chi-square) and multivariate using logistic regression. Results: Showed that the risk factors that significantly increased the incidence of low birth weight babies were maternal age with adjusted OR(AOR) = 6.8 (95% CI:1.87-25.0), birth spacing with AOR = 6, 5(95%CI: 1,78-24.2), working mother status with AOR=4,6(95%CI:1,44-14,9), , malaria co-morbidities with AOR=3.9(95 %CI: 1,21-12,7) and the quality of ANC is less with AOR= 3,5 (95% CI: 1,11-11,3). Conclusion: Age < 20 or 35 years, birth spacing, maternal occupation, malaria comorbidities and poor quality of antenatal care are risk factors for the occurrence of low birth weight in Ende Regency.